Prognostic value of neutrophil-lymphocyte ratio, absolute lymphocyte count, and thrombocyte-lymphocyte ratio in predicting the outcomes of tetralogy of fallot primary repair - Siagian, Sisca Natalia; Christianto, Christianto (Frontiers in Cardiovascular Medicine, 2025)
Tetralogy of Fallot (ToF) is a chronic hypoxic condition that increases the risk of inflammatory responses during surgery. However, many inflammatory biomarkers used to predict surgical outcomes are costly and not widely accessible. This single-center, retrospective observational study aimed to compare the prognostic value of neutrophil-lymphocyte ratio (NLR), absolute lymphocyte count (ALC), and thrombocyte-lymphocyte ratio (TLR) in predicting outcomes of ToF primary repair. Between January 2020 and December 2022, 501 patients underwent ToF primary repair. Our findings revealed low postoperative reoperation (6.5%) and 30-day mortality (4.7%) rates, but prolonged LOS (92.2%) and a high complication rate (84%), with grade IVa (27.9%) and grade I (26.4%) complications being the most common. Elevated NLR (r = 0.132, p = 0.014), female gender (r = 0.117, p = 0.027), associated diagnoses (r = 0.104, p = 0.047), and prolonged surgical duration (r = 0.176, p = 0.001) were linked to higher complication burdens, though the correlations were weak. Among the three indexes, preoperative NLR demonstrated the strongest predictive value for complications, despite its low sensitivity and specificity. Given its accessibility and cost-effectiveness, NLR may serve as a useful tool for identifying high-risk patients and improving postoperative monitoring. Future multicenter prospective studies are necessary to validate the prognostic value of preoperative NLR under standardized conditions, across a broader patient population, and with more comprehensive confounding variables adjustments, ultimately improving ToF surgical outcomes (Clinical Trial NCT05976204).